1998
DOI: 10.3109/10826089809059324
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Street Crime in Miami: An (Almost) Twenty-Year Retrospective

Abstract: Researchers at the University of Delaware have been conducting field studies of drug use and crime in Miami, Florida, since 1977. This paper reviews this research and its contributions to understanding drugs-crime relationships. Early studies tested mechanisms for accessing street populations of heroin users and assessing the nature and extent of their drug use and criminality. Subsequent studies targeted a variety of crime-involved heroin and cocaine users, including women as well as men, serious delinquents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Official crime records are known to underestimate the actual prevalence of criminal activity (Kirk, 2006), and especially for "victimless" offenses (e.g., sale and dealing in drugs or driving without a license), the priorities of the public authority have a great impact on the number and type of cases being prosecuted (Thorsen et al, 2009). There is a low risk of arrest for many of the income-generating crimes committed by heroin users (Inciardi & Pottieger, 1998), and drug selling is also more likely to lead to arrest than offenses such as burglary or robbery (Reuter, 1997). For this reason, it is likely that large amounts of the crime committed by our population are undetected.…”
Section: Discussionmentioning
confidence: 99%
“…Official crime records are known to underestimate the actual prevalence of criminal activity (Kirk, 2006), and especially for "victimless" offenses (e.g., sale and dealing in drugs or driving without a license), the priorities of the public authority have a great impact on the number and type of cases being prosecuted (Thorsen et al, 2009). There is a low risk of arrest for many of the income-generating crimes committed by heroin users (Inciardi & Pottieger, 1998), and drug selling is also more likely to lead to arrest than offenses such as burglary or robbery (Reuter, 1997). For this reason, it is likely that large amounts of the crime committed by our population are undetected.…”
Section: Discussionmentioning
confidence: 99%
“…Committing violent crimes was not, as we assumed, associated with frequent alcohol use. Remarkably, violent crime was more likely uncommon among the crack users in this study (3.8%, and 9.7% of criminals), given the strong association between crack cocaine use and violence found in the literature [1,24,59]. We can speculate that, again, the advanced age of crack users in our sample played a major role in this finding [38] as well as systemic circumstances associated with the Dutch crack market that differ from those typically found in the USA, especially those described for the so-called ‘crack era' [24].…”
Section: Discussionmentioning
confidence: 99%
“…Criminality among drug users has been the subject of many studies, especially in relation to drugs like (crack) cocaine and heroin [1,2,3,4,5]. Research by the criminal justice system has found large proportions of arrestees who use these drugs; these individuals have illegal incomes of up to 4 times higher than arrestees who are not using illicit drugs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The entrenched HIV epidemic in Miami is linked to high rates of drug abuse in these areas. For almost four decades, Miami has been both a port of entry and corridor community for the trafficking of illegal drugs, and it has been a well-known epicenter for the abuse of cocaine, crack, heroin, and other drugs (Inciardi & Pottieger 1998). …”
mentioning
confidence: 99%